Dorsal root ganglia volume: normative values, correlation with demographic determinants and reliability of three different methods of volumetry - Kronlage, Moritz; Fischer, Thomas David; Behnisch, Rouven; Schwarz, Daniel; Bäumer, Philipp; Münch, Véronique; Heiland, Sabine; Bendszus, Martin; Godel, Tim (Diagnostics, 2022)
Background: Dorsal root ganglia (DRG) volume assessment by MR-Neurography (MRN) has evolved to an important imaging marker in the diagnostic workup of various peripheral neuropathies and pain syndromes. The aim of this study was (1) to assess normal values of DRG volume and correlations with demographic determinants and (2) to quantify the inter-reader and inter-method reliability of three different methods of DRG volumetry. Methods: Sixty healthy subjects (mean age: 59.1, range 23-79) were examined using a 3D T2-weighted MRN of the lumbosacral plexus at 3 Tesla. Normal values of DRG L3 to S2 were obtained after exact volumetry based on manual 3D segmentation and correlations with demographic variables were assessed. For the assessment of inter-reader and inter-method reliability, DRG volumes in a subset of 25 participants were measured by two independent readers, each applying (1) exact volumetry based on 3D segmentation, (2) axis-corrected, and (3) non-axis-corrected volume estimation. Intraclass correlation coefficients were reported and the Bland-Altman analysis was conducted. Results: Mean DRG volumes ranged from 124.8 mm3 for L3 to 323.3 mm3 for S1 and did not differ between right and left DRG. DRG volume (mean of L3 to S1) correlated with body height (r = 0.42; p = 0.0008) and weight (r = 0.34; p = 0.0087). DRG of men were larger than of women (p = 0.0002); however, no difference remained after correction for body height. Inter-reader reliability was high for all three methods but best for exact volumetry (ICC = 0.99). While axis-corrected estimation was not associated with a relevant bias, non-axis-corrected estimation systematically overestimated DRG volume by on average of 15.55 mm3 (reader 1) or 18.00 mm3 (reader 2) when compared with exact volumetry. Conclusion: The here presented normal values of lumbosacral DRG volume and the correlations with height and weight may be considered in future disease specific studies and possible clinical applications. Exact volumetry was most reliable and should be considered the gold standard. However, the reliability of axis-corrected and non-axis-corrected volume estimation was also high and might still be sufficient, depending on the degree of the required measurement accuracy.
Gesehen am 19.08.2022